Paparan CO pada Lingkungan Kerja dan Dampak terhadap Kesehatan - Izzati, Marwah Aulia; Soeprihatini, Retno Ariza; Komala, Ramadhana (CV. Jasa Sukses Abadi, 2024)
Air pollution is waste produced from human activities in meeting their needs can become air pollution that has an impact on disorders and diseases due to air pollution, especially in the respiratory tract due to long-term exposure. Carbon monoxide is one of the toxic substances resulting from the process of imperfect combustion and driving fumes. Exposure to carbon monoxide in the respiratory system results in the formation of a bond of carbon monoxide (CO) with hemoglobin to become COHb. Carbon monoxide (CO) and O2 compete to occupy the same binding site in Hb, but the affinity of Hb for CO is 240 times greater than for O2. Other factors that cause the formation of COHb in the blood besides exposure to CO pollution such as smoking habits. chemicals contained in each cigarette, some of which are toxic, including CO gas. A person who smokes one pack of cigarettes/day can have a COHb level of 3% to 6% in the blood, with two packs/day the level can be 6% to 10% and as much as 20% with three packs/day. The easiest effort to avoid risk is the use of proper personal protective equipment. In this case, the use of masks can be useful because the exposure process is through inhalation. This study is a literature review that collects and evaluates research using Google Scholar with the keywords